Application of positron annihilation as a nondestructive method of checking the quality of materials - Fedorov V. A.; Prilipko V. I.; Prokop'ev E. P.; Arefyev (Afef'ev, Arefiev) K. P. Konstantin Petrovich (1982, 1982)
Title screen